Semiotic Analysis of Chinese Folk Architecture in Modern Planning - Min Li; Xian Hu (Prostor)
The study aims to explore the semiotics of the genetic symbols of Chinese folk architecture as the basis for representing the symbolic and mythological events of national history in the contemporary reconstruction of traditional settlements. The questionnaire-based survey, which involved 227 city dwellers and 239 residents of traditional villages, was used to assess architectural objects. As a result, the study justified the use of Chinese folk architecture symbols when implementing the Chinese state program for the traditional village revival, as well as when solving the problems of preserving the original historical architectural heritage in Western Chinatowns and in China itself. The mentioned symbols can be used to determine the conceptual approaches in architectural planning of traditional Chinese rural settlements.